Twice-Daily Oral Zinc in the Treatment of Patients With Coronavirus Disease 2019: A Randomized Double-Blind Controlled Trial. (4th November 2022) - Ben Abdallah, Saoussen; Mhalla, Yosra; Trabelsi, Imen; Sekma, Adel; Youssef, Rim; Bel Haj Ali, Khaoula; Ben Soltane, Houda; Yacoubi, Hajer; Msolli, Mohamed Amine; Stambouli, Nejla; Beltaief, Kaouthar; Grissa, Mohamed Habib; et al.
Abstract: Background: Zinc supplementation has been considered a potential therapy for coronavirus disease 2019 (COVID-19). We aimed to examine zinc efficacy in adult patients with COVID-19 infection. Methods: We conducted a prospective, randomized, double-blind, placebo-controlled multicenter trial. Patients who were tested positive for COVID-19 without end-organ failure were randomized to oral zinc (n = 231) or matching placebo (n = 239) for 15 days. The primary combined outcome was death due to COVID-19 or intensive care unit (ICU) admission ≤30 days after randomization. Secondary outcomes included length of hospital stay for inpatients and duration of COVID-19 symptoms with COVID-19–related hospitalization for outpatients. Results: 190 patients (40.4%) were ambulatory and 280 patients (59.6%) were hospitalized. Mortality at 30 days was 6.5% in the zinc group and 9.2% in the placebo group (OR: .68; 95% CI .34–1.35); ICU admission rates were, respectively, 5.2% and 11.3% (OR: .43; 95% CI .21–.87). Combined outcome was lower in the zinc group versus the placebo group (OR: .58; 95% CI .33–.99). Consistent results were observed in prespecified subgroups of patients aged <65 years, those with comorbidity, and those who needed oxygen therapy at baseline. Length of hospital stay was shorter in the zinc group versus the placebo group (difference: 3.5 days; 95% CI 2.76–4.23) in the inpatient group; duration of COVID-19 symptoms decreased with zinc treatment versus placebo in outpatients (difference: 1.9 days; 95% CI .62–2.6). No severe adverse events were observed during the study. Conclusions: Our results showed that, in COVID-19 patients, oral zinc can decrease 30-day death, ICU admission rate and can shorten symptom duration. Clinical Trials Registration. ClinicalTrials.gov, NCT05212480. Abstract : In this randomized controlled trial, we demonstrated that zinc administered orally to hospitalized patients with COVID-19 could prevent intensive care unit admission and reduce the hospital length of stay. For outpatients, zinc could shorten symptom duration.